A case study of a community center project based on appropriate technology as a community capacity building of underdeveloped country. Issue 2 (4th March 2019) - Lee, Byungyun; Na, In Su
ABSTRACT: This study is a case study on community center planning in Gondrapa Village of Mymensingh City, Bangladesh, where the urban poor are densely populated. The goals of the plan are to build the capacity of the community, improve the local sanitation level, improve gender equality, and create a more sustainable urban environment. Particularly, this project was judged that the process of project planning and construction through participatory design and implementation with local residents contributed to enhance the local residents' pride and the consciousness of the residents themselves.